Analysis of Static Narrowband On-Body Channel Polarization Distribution at 2.4 GHz - Lingfeng Liu; Peng Zhang; Xiaonan Wang; Xiaoyan Zhang; Nan Jiang (International Journal of Antennas and Propagation)
The polarization of on-body propagation channels has shown significant spatial selectivity and full-space distribution in numerous measurements due to the near-field characteristics and strong body scattering effect. To get a comprehensive image of such polarization distribution, in this work, we measured polarized on-body channels on static body at 2.4 GHz by monopole antennas, where standing and sitting postures are included. The polarization of the measured on-body antennas covers the full-space in Z-, H-, and V-direction relative to the skin of the body. Consequently, an extended cross-polarization discrimination (XPD) is also proposed to describe the depolarization and copolarization in the measurements. In the statistical characteristics of the channels, the V-polarization direction of the receiving antenna is more conducive for receiving signal and reducing the path losses. The results show that strong depolarization of on-body channels is more easily caused in sitting posture due to scattering effects from the legs. Simplified finite-difference-time-domain (FDTD) simulations are conducted to investigate the field polarization distribution of point sources on a static torso in cylindrical shape. The simulation results are in general consistent with the analysis of measured on-body channels.